Global dynamics of a vector-borne disease model with latency and saturating incidence rate - Rahman, Ashrafur (International Journal of Advanced Mathematical Sciences, 2014)
This paper deals with a vector-borne disease model containing latency and nonlinear incidence rates. Global analysis is completely determined by suitable Lyapunov functionals. We explicitely determine the basic reproduction number and find that if this number is less than one then disease dies out, but if the number is larger than one, the disease causing strain become endemic. The study shows that the latency delay explicitely in°uence the disease persistence. Keywords: Latency, saturating incidence, basic reproduction number, global attractivity, Lyapunov functionals.